A comparative analysis of the European Union member states in terms of public spending on environmental protection in 2004-2017 - Barbara Pawełek (European Journal of Government and Economics (EJGE), 2020)
The main purpose of the paper is to present the results of the comparative analysis of the member states of the European Union in terms of expenditure on environmental protection made by the public sector. An additional purpose of the paper is to verify whether there is convergence in public spending on environmental protection of the member states of the European Union. In the study, the convergence models and cluster analysis were used. The research results indicate, among others, that there was convergence in total public spending on environmental protection in the member states of the European Union in 2004-2017, and that the structure of the member states in terms of amounts of public spending on various aspects of environmental protection in 2004-2010 differed from the structure of the member states determined for the years 2011-2017.
Keywords: C38; H50; Q01; 330; convergence; environmental protection; EU member states; public spending